A Novel Long Noncoding RNA lincRNA00892 Activates CD4+ T Cells in Systemic Lupus Erythematosus by Regulating CD40L - Liu, Xiao; Lin, Jinran; Wu, Hao; Wang, Yilun; Xie, Lin; Wu, Jinfeng; Qin, Haihong; Xu, Jinhua (Frontiers in Pharmacology, 2021)
The mechanism of CD4+ T cell dysfunction in systemic lupus erythematosus (SLE) has not been fully understood. Increasing evidence showed that long noncoding RNAs (lncRNAs) can regulate immune response and take part in some autoimmune diseases, while little is known about the lncRNA expression and function in CD4+ T of SLE. In our present study, we found a total of 1887 lncRNAs and 3375 mRNAs aberrantly expressed in CD4+ T cells of SLE patients compared to healthy controls by microarray. Among them, lincRNA00892 and CD40L were further confirmed upregulated in CD4+T cells of SLE patients by qRT-PCR. The lncRNA-mRNA co-expression network analysis indicated that CD40L was a potential direct target of lincRNA00892. Overexpression of lincRNA00892 upregulated CD40L protein level while exert little influence on CD40L mRNA level. In addition, lincRNA00892 could promote the activation of CD4+T cells. Furthermore, lincRNA00892 led to the activation of B cells and subsequent secretion of IgG in a CD4+T cell dependent manner. Finally, hnRNP K was found to be among the proteins pulled down by lincRNA00892, and hnRNP K could bind to lincRNA00892 or CD40L directly. In conclusion, our results showed that the lncRNA expression profile is altered in CD4+ T cells of SLE. LincRNA00892 possibly contributed to the pathogenesis of SLE by targeting hnRNP K and subsequently upregulating CD40L expression to activate CD4+T and B cells. These provided us a potential target for further mechanistic studies of SLE pathogenesis.